2016
DOI: 10.1007/978-3-319-47665-0_43
|View full text |Cite
|
Sign up to set email alerts
|

Topic Switch Models for Dialogue Management in Virtual Humans

Abstract: Abstract. This paper presents a novel data-driven Topic Switch Model based on a cognitive representation of a limited set of topics that are currently in-focus, which determines what utterances are chosen next. The transition model was statistically learned from a large set of transcribed dyadic interactions. Results show that using our proposed model results in interactions that on average last 2.17 times longer compared to the same system without our model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The idea is to have a system capable of perceiving emotions from humans and reacting based on the perceived emotions (e.g., virtual humans [4]). By understanding the humans' emotions from the social conversation, the system provides more colourful interaction to humans [4,7,13,14]. Recognising emotions can be done with several features, such as: brainwave [15], heartbeat [16], voice prosody (e.g., the stress, rhythm and intonation of speech [17], facial expressions [18,19], and body gestures [20].…”
Section: Emotions Recognitionmentioning
confidence: 99%
“…The idea is to have a system capable of perceiving emotions from humans and reacting based on the perceived emotions (e.g., virtual humans [4]). By understanding the humans' emotions from the social conversation, the system provides more colourful interaction to humans [4,7,13,14]. Recognising emotions can be done with several features, such as: brainwave [15], heartbeat [16], voice prosody (e.g., the stress, rhythm and intonation of speech [17], facial expressions [18,19], and body gestures [20].…”
Section: Emotions Recognitionmentioning
confidence: 99%
“…The idea is to have a system capable of perceiving emotions from humans and reacting based on the perceived emotions. By understanding the humans' emotions from the social conversation, the system provides more colourful interaction to humans [8,4,9,5]. Recognising emotions can be done with several features, such as: brainwave [10], heartbeat [11], voice prosody [12], facial expressions [13,14], and body gestures [15].…”
Section: Emotions Recognitionmentioning
confidence: 99%
“…Even though the TDT project was more about information retrieval than dialogue, the way of talking about topics as events can be useful for spontaneous casual conversation, because people talk about the news often when meeting. Zhu et al (2016) made a probabilistic topic switch model for an agent to match topics to user utterances and talk about related topics. The model took three things into account: topic frequency, concurrency and adjacency.…”
Section: Knowledge Basementioning
confidence: 99%
“…The model was trained on an annotated corpus, with a predefined list of topics. Zhu et al (2016) conducted an experiment and found that their topic switch model was more entertaining for users to interact with than without it. However, the granularity of topics was occasionally incorrect.…”
Section: Knowledge Basementioning
confidence: 99%